MOTIVASI PETANI KAKAO BERGABUNG DALAM KELOMPOK TANI DI KELURAHAN KAPALO KOTOKECAMATAN PAYAKUMBUH SELATAN(Studi Kasus Kelompok Tani Tanjung Subur) - Hidayanti, Nurmia; Sayamar, Eri; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) to know the intrinsic motivation of cocoa farmers to joined with Tanjung Subur Farmer Group; and (2) to know extrinsic motivation of cocoa farmers to joined with Tanjung Subur Farmer Group. This research carried out by survey method to 27 cocoa farmers who have became members of Tanjung Subur Farmer Group in Kapalo Koto Village South Payakumbuh District Payakumbuh City. Data analysis was done quantitative descriptively and used Likert’s Summated Rating Scale (SLRS). The result showed that the intrinsic motivation of cocoa farmers to joined with Tanjung Subur Farmer Group consists of responsibility, advancement, achievement, and rewards who categorized as “High” with a total score of 3,70. Responsibility and advancement indicators with a score of 4,21 categorized “Very High”, achievement indicator with a score of 3,10 and rewards indicator with a score of 3,27 categorized “High Enough”. The extrinsic motivation of cocoa farmers to joined with Tanjung Subur Farmer Group consists of compensation, status, supervision, and competition who categorized as “High” with a total score of 4,04. Compensation and status indicators with a score of 4,20 categorized “Very High”, supervision indicator with a score of 4,09 and competition indicator with a score of 3,27 categorized “High Enough”   Keywords: Cocoa farmer, Farmer group, intrinsic motivation, extrinsic motivation